(untitled) (International journal of artificial intelligence, 2026)
This article explores the role and significance of ethics and values in a digital society. It analyzes how the rapid development of digital technologies affects human behavior, communication, and responsibility in the online environment. The study emphasizes the importance of preserving human values in the digital age, highlighting key ethical issues such as respect, honesty, and the responsible use of information.